IDENTIFICATION AND MOLECULAR CHARACTERIZATION OF Escherichia coli O157:H7 ISOLATED FROM THE GREAT ZAB RIVER IN ERBIL AND INHIBITORY EFFECT OF SILVER NANOPARTICLES - Abdulqader, Aras Jamal; Hamid, Bahaddin S. (Science Journal of University of Zakho, 2026)
Microbial pathogens may be introduced into surface water sources through agricultural runoff, sewage discharge, or stormwater, and such contamination poses a significant threat to public health. Escherichia coli is a bacterial species that inhabits several environments, including the gastrointestinal tract of humans and warm-blooded animals. E. coli, especially the O157:H7 serotype, is an important indicator species for fecal contamination and possible pathogenicity. The objective of this study was to recover E. coli O157:H7 from the Great Zab River in Erbil and to investigate its virulence factors and the susceptibility of isolates to silver nanoparticles (AgNPs). 150 water samples, from different sources, were bacteriologically analyzed using Sorbitol MacConkey agar. The presumptive isolates were identified by means of biochemical tests and the VITEK 2 system. Three (2%) E. coli O157:H7 were isolated from the samples. Sensitivity of isolates to various AgNP concentrations was demonstrated by antimicrobial assays. One isolate was confirmed by sequencing 16S rRNA gene. PCR detected the presence of the eae gene in all isolates, the absence of shiga toxins, and in one isolate, the fliC gene was observed. These results demonstrate the pathogenic E. coli O157:H7 in the river and the potential application of AgNPs as an antimicrobial in such water bodies.